Setting Standards for Communication and Governance : The Example of Infrastructure Projects - Hass, Lawrence; Mazzei, Leonardo; O'Leary, Donal (Washington, DC: World Bank, 2012)
This paper outlines a number of practical initiatives to strengthen the role of development communication in infrastructure projects. The authors aim to facilitate better quality projects and to build consensus on the type of governance reforms needed to fight corruption, drawing on the experience of development agencies like the World Bank and Transparency International, the leading anticorruption NGO. The paper starts by characterizing corruption vulnerabilities in infrastructure and proceeds to illustrate where communication has added value on a number of recent projects, both in respect to making the projects more sustainable and by incorporating anti-corruption measures into the project preparation and implementation phases. It draws on examples of mainly World Bank supported projects from the road, transport, power and water sectors in different governance contexts. Part of the intellectual challenge in mainstreaming development communication in the case of infrastructure is to bridge the infrastructure and communication paradigms. Finally, the paper suggests that today, from the perspective of the infrastructure practitioner and the development practitioner in general, development communication is at the same crossroads as environmentally sustainable development was in the early 1990's-but in a new context and perhaps with more urgent drivers for mainstreaming.